(untitled) - The World Bank in Vietnam; Vietnam Development Information Center (Hà Nội, 2007)
Contents of the book is social and economic context; Vietnam's vision for 2010; bank's group track record; world bank group country partnership strategy; delivering the bank group strategy; managing risks.
Keywords: Developing countries,Tình trạng kinh tế xã hội; Economic conditions; Viet Nam,Việt Nam